Analysis of agricultural holdings and access to public policies in agrarian reform projects in the microregion of Andradina (SP) - Silva, Flaviana Cavalcanti da; Sant'Ana, Antonio Lazaro [UNESP]; Maia, Ana Heloisa (Univ Federal Roraima, 2023)
This work characterizes and discusses aspects pertinent to the productive systems exploited by families based in the Microregion of Andradina / SP, as well as analyzes the access of these to the main public policies focused on family agriculture. Characterized by a qualitative -quantitative approach, field research included 30 producers belonging to eight settlements in the Microregion. On -site visits were performed, using as data collection instruments, mainly questionnaires and direct observation. The preponderance of dairy cattle raising in relation to income generation and production for self -consumption for the producers surveyed was verified (77% exploit the activity); however, the seasonality of production raises concerns, given the strong reduction in milk production during the dry season, observed in 80% of the analyzed cases. Allied to the dairy activity, among the public surveyed, stand out the strategies based on polyculture and the exploitation of crops that have relatively low production costs and do not require specific infrastructure. The need for public policy instruments in the Andradina Microregion to involve efforts that could effectively contribute to the expansion of the possibilities of socioeconomic reproduction strategies of the established producers; so that they are not doomed to the dairy cattle and to small areas of olericultura, in view of the strong limitations related to the available infrastructure and the weaknesses in the field of technical assistance and rural extension, observed in the agrarian reform spaces of the Microregion .
Keywords: Family agriculture; Public policies; Rural settlements